Engineering applications of Global Earth Information System (GEIS) (Journal of Nepal Geological Society, 2000)
Database is a systematic collection and storage of certain base information related in space and time. Any such database that is a systematic collection and storage of certain base information needs further intelligent analysis for the engineering application. Also, the organised listings, sorting, analyses, and instant retrieval of this ground information are highly useful in management. We developed the new information system named Global Earth Information System (GEIS) as a powerful assistant for researchers to query, analyse, and map data in support of the decision-making process. The real world information can be collected of thematic layers that can be analysed and linked together by geography. Secondary data are induced from original data as a representative of area or time.